A high efficient semi-open system for fresh water production from atmosphere. (1st November 2017) - Wang, J.Y.; Wang, R.Z.; Wang, L.W.; Liu, J.Y.
Abstract: A high efficient semi-open system of fresh water production is established with novel consolidated composite sorbent. This device collects 14.7 kg of water with packing 40.8 kg of consolidating sorbents in 0.4 × 0.4 × 0.6 m size of sorbent bed. The consolidated active carbon felt combined with LiCl sorbent and its corrugated filling mode are invented, which has large cycle sorption quantity, excellent heat transfer performance, and enough mass transfer channels. The sorption and desorption performances of device are tested at different experiments conditions. In sorption process, 14.7 kg, 13.6 kg, and 12.5 kg fresh water is obtained under the condition of 85%, 75%, and 65% RH; while in desorption process, 14.5 kg, 13.6 kg and 0 kg water is got under the condition of 90 °C, 77 °C, and 60 °C respectively. This appliance ensures the large adsorbing capacity at 23 °C and 90% RH, and achieves a large amount of desorption (0.65 g/g) between 70 and 80 °C with 8.8 Pa flow resistance. The pressure drop and velocity distribution of the actual operation in the unit structure of sorbent bed are simulated, and the water mass is calculated to analyze the sorption and desorption performances of the device. Highlights: A high efficient semi-open system of fresh water production is established. 14.7 kg water is collected and it costs 1 kW‧ h energy to get 1 kg water. 40.8 kg ASLI sorbents are packed in 0.4 × 0.4 × 0.6 m size due to the novel structure. In sorption process, the higher the relative humidity, the more the water uptake. In desorption process, the higher the temperature, the more the water collected.